2009
DOI: 10.1074/mcp.m800518-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of Protein Inventories Obtained from Formalin-fixed Paraffin-embedded and Frozen Tissue in Multidimensional Liquid Chromatography-Tandem Mass Spectrometry Shotgun Proteomic Analysis

Abstract: Formalin-fixed paraffin-embedded (FFPE) tissue specimens comprise a potentially valuable resource for retrospective biomarker discovery studies, and recent work indicates the feasibility of using shotgun proteomics to characterize FFPE tissue proteins. A critical question in the field is whether proteomes characterized in FFPE specimens are equivalent to proteomes in corresponding fresh or frozen tissue specimens. Here we compared shotgun proteomic analyses of frozen and FFPE specimens prepared from the same c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
207
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 189 publications
(244 citation statements)
references
References 30 publications
33
207
4
Order By: Relevance
“…Whereas metabolite profiles are subject to perturbation by ischemia associated with tissue collection, protein abundance is stable and thus provides a quantifiable signature of metabolic reprogramming (52,66). This approach should thus be of broad utility to investigate the relationship between cancer metabolic phenotypes, metastasis and response to therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas metabolite profiles are subject to perturbation by ischemia associated with tissue collection, protein abundance is stable and thus provides a quantifiable signature of metabolic reprogramming (52,66). This approach should thus be of broad utility to investigate the relationship between cancer metabolic phenotypes, metastasis and response to therapies.…”
Section: Discussionmentioning
confidence: 99%
“…eral studies have shown that although the individual peptides retrieved and identified from fresh-frozen and FFPE tissues may differ, the biological information obtained from both types of material in terms of number of proteins identified, cellular location and molecular function is very similar (5)(6)(7)(8)(9)(10). A number of proteomics studies were reported, which used untargeted MS on FFPE tissues to compare diseased and healthy samples in the search for potential novel biomarkers (10).…”
mentioning
confidence: 99%
“…[15][16][17][18][19][20][21]). Due to the harsh chemicals involved in the preparation of such samples, the proteins would not be expected to be intact or active, thus such studies are limited to protein identification.…”
Section: Introductionmentioning
confidence: 99%